Ionic liquid-SnO2 nanoparticle hybrid electrolytes for secondary charge storage devices: Physicochemical and electrochemical studies. (22nd February 2018) - Dutta, Bula; Deb, Debalina; Bhattacharya, Subhratanu
Abstract: A series of nanoscale hybrid ionic fluids (NHIFs) has been prepared by tethering 1-ethyl-3-(3-trimethoxysilylpropyl)-imidazolium bis(trifluoromethanesulfonyl) imide ionic liquids to the surface of SnO2 nanoparticle, at different grafting densities. Investigations reveal that SnO2 nanocores with uniform particle size of 14–17 nm are uniformly dispersed in different NHIF matrices through strong covalent attachment. Thermal stability and mechanical properties of NHIFs are found to improve with increasing grafting density. Temperature dependent electrochemical cycling behaviour of NHIF at different grafting densities are thoroughly investigated. In comparison to pure ionic liquid, the hybrid ionic fluids show substantial enhancement in electrochemical properties, which further improve with increasing grating density. The electrochemical cell containing NHIFs as electrolytes show very good capacitance retentivity (>90%) and long term cyclic stability above room temperature. Results obtained from the study demonstrate the applicability of these hybrid ionic fluids as promising electrolytes in secondary charge storage devices. Graphical abstract: Highlights: Imidazolium based nanoscale hybrid ionic fluids are prepared with different grafting density. Thermal, mechanical and temperature dependent electrochemical properties are studied. The electrochemical properties of NHIFs strongly depends upon grafting density. Hybrid fluids show wide electrochemical window with long term cycling stability.